Self Efficacy Dalam Pemecahan Masalah Matematis : Studi Kasus Siswa SMP Dalam Memecahkan Soal Teorema Pythagoras - Nova Anwari Tama Putri; Ramlah; Indra Budiman (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Self-efficacy is an important factor that influences students' success in solving mathematical problems. This study aims to describe the differences in self-efficacy characteristics between students with high and low self-efficacy scores in solving mathematical problems on the topic of the Pythagorean Theorem. This research employed a qualitative approach involving two junior high school students selected based on the results of a self-efficacy questionnaire. Data were collected through questionnaires, mathematical problem-solving tests, unstructured interviews, observations, and time triangulation to obtain accurate and in-depth data. The research instruments included a self-efficacy questionnaire based on Bandura's theory with seven indicators, as well as a problem-solving test based on Polya’s stages. Data analysis was conducted through data reduction, data display, and drawing conclusions interactively until the data were saturated. The results of the study showed that students with high self-efficacy scores were able to utilize mastery experiences, had stable self-confidence and expectations of success, were able to develop structured strategies, and could recover from failure with positive social support. These students also used the success of others as motivation in solving problems. In contrast, students with low self-efficacy scores showed less stable self-confidence, were more dependent on others for assistance, and had difficulties in developing effective problem-solving strategies. Their self-efficacy also tended to decrease easily when facing failure.